Ukrainian wedding nominations of the newly-weds with the semantics of superiority of power - Заверющенко, Ольга Леонідівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article investigates Ukrainian wedding nominations of the newly-weds with the semantics of superiority of power, which fill one of the most considerable places in the linguospace of the Ukrainian wedding. From the materials of folklore records, dialect dictionaries there can be seen the origin of the named nomens, established the role and place of such nominations in the sphere of concepts of the Ukrainian wedding, there comes out the connection between those terms and wedding images, that are endowed with agrarian, zoomorphous and cosmogonic symbolism, other wedding participants’ images.